HLA Antigen Distribution in Renal Transplant Recipients and Donors - Tuladhar, A; Shrestha, S; Raut, P P; Bhandari, P; Shrestha, P (Journal of Nepal Health Research Council, 2014)
Background: HLA typing analysis is important in renal transplant patient. This study is the first report from Nepal to find out distribution of HLA A, B, DR antigen in live related renal transplant recipients and donors from Nepal. The aim of this study was to investigate the distribution of HLA in the live related renal transplant recipients and donors of Nepal.Methods: In a retrospective study, HLA patterns were defined in 100 live related renal transplant recipients and donors. One year study is done from June 2011 to May 2012. The study was done by using sequence specific oligonucleotides primers and polymerase chain reaction and assay. Allele frequencies were obtained by direct counting.Results: A total of 12 HLA-A, 15 HLA-B and 13 HLA-DRB1 alleles were identified at the four-digit level in the live related renal transplant recipients and donors of Nepal. High frequency alleles were HLA-A*11 (34.5%), A*24 (17%), A*33 (13%); HLA-B*15(27%), B*35(19%), B*40 (10%); HLA-DRB1*15 (33.5%), DRB1*12 (21.4%) and DRB1*04 (7.32%).Conclusions: These results showed considerable heterogeneity in both HLA class I and class II antigens. To reduce the risk of allograft rejection, transplantation from HLA matched donors is recommended.Keywords: allele; HLA antigen distribution; renal transplant.